Selection and management design for optimization of forest type in Zhejiang - LIU An-xiang; DU Qun (浙江大学学报. 农业与生命科学版)
According to the demand of modern forestry and the status of lacking in wood resources in Zhejiang Province, the most optimal forest type that is ecologically and economically beneficial was selected and object to sustained management. Applying the principle of landscape ecology, the management of mixed forest of Masson's pine and broad-leaved trees, which is known as the most optimal forest type in Zhejiang, was studied and its management model was propounded. In the same time, the traditional model of management for mixed forest of Masson's pine and broad-leaved trees as adopted by local peasants in Zhejiang was examined and discussed. The aim of this paper is to provide the methods of selection and management of the most optimal forest.